Food for You (F4U) Mobile Charity Application - Masrom, Suraya; Sani Abd. Rahman, Abdullah; Norliyana Azahar, Farah; Omar, Nasiroh (International Journal of Engineering and Technology, 2018)
The Food for You (F4U) mobile charity application has been developed with objective to ease the burden of impecunious peoples, who need foods to continue living. Simultaneously, the application is also beneficial in reducing the food waste problem. While there exists a few of mobile charity applications, none of them provides connections between the needy, donators and food suppliers as to resolve the food waste problem. This paper provides a features comparison study among several charity mobile applications, defining the limitation of the application and introduces the F4U mobile charity application. The system flow and general architecture are also described in this paper, including the usability test of the system. Results from the usability study has indicated that the system is easy to use and able to decrease 49% of food waste at the selected testing area.Â Â Â